2019
DOI: 10.1186/s13287-019-1241-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen suppresses glioblastoma growth via inducing the glioma stem-like cell differentiation

Abstract: Background Glioblastoma (GBM) is the most common type of primary malignant brain tumor. Molecular hydrogen has been considered a preventive and therapeutic medical gas in many diseases including cancer. In our study, we sought to assess the potential role of molecular hydrogen on GBM. Methods The in vivo studies were performed using a rat orthotopic glioma model and a mouse subcutaneous xenograft model. Animals inhaled hydrogen gas (67%) 1 h two times per day. MR imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
4
29
0
Order By: Relevance
“…These markers were also analyzed in relative adherent cells to highlight the differences with respect to neurosphere-forming cells (Table 1). In accordance with previous reports [8,63,64], the percentages…”
Section: Phenotypic Analyses Of Neurosphere-derived Cellssupporting
confidence: 92%
“…These markers were also analyzed in relative adherent cells to highlight the differences with respect to neurosphere-forming cells (Table 1). In accordance with previous reports [8,63,64], the percentages…”
Section: Phenotypic Analyses Of Neurosphere-derived Cellssupporting
confidence: 92%
“…In vitro study indicated that hydrogen gas inhibited several markers involved in stemness, resulting in the suppression of sphere formation, cell migration, invasion, and colony formation of glioma cells. By inhaling hydrogen gas (67%) 1 h, 2 times per day, the GBM growth was significantly inhibited, and the survival rate was improved in a rat orthotopic glioma model, suggesting that hydrogen might be a promising agent in the treatment of GBM (100).…”
Section: Hydrogen Gas Exhibits Potential In Cancer Treatmentmentioning
confidence: 99%
“…The invasive properties of glioblastoma are a key problem for curative treatment if a surgical resection is impracticable. The experimental in vivo studies showed that H 2 inhalation could suppress glioblastoma tumor growth, prolonging the survival of mice with glioblastoma [ 56 ]. In a recent study, data show that, in a patient diagnosed with lung cancer with metastases, H 2 gas monotherapy was associated with a significant effective control of tumors [ 57 ].…”
Section: Protective Properties Of Molecular Hydrogen: Potential Anmentioning
confidence: 99%